Identifying income and wealth-poor households in the euro area - Philip Müller; Tobias Schmidt (Deutsche Bundesbank, 2015)
In this paper, we analyse different measures of asset and income poverty using micro-data for 15 euro area countries from the 2010 Household Finance and Consumption Survey (HFCS). We are particularly interested in the way in which specific definitions of income and wealth poverty affect the number and socio-demographic characteristics of poor households, as well as their portfolio composition and consumption expenditure. We find that adding wealth to the poverty definition mainly influences the percentage of poor households but has a limited effect on the documented socio-demographic composition, portfolio structure and food consumption of poor households compared to the patterns under a pure income poverty measure. Within each country, we document some heterogeneity with regard to the percentage of poor households across different poverty measures. However, across countries, the percentage of households in poverty for any given indicator is relatively homogenous. We find the typical socio-demographic patterns for poor households: the risk of being income and/or wealth-poor is, in almost all countries, higher for smaller households, households with a less educated head and single-parent households. We also show that the percentage of female, old and retired reference persons is higher for poor households than for the population at large. Additionally, the participation rates in real and financial assets for poor households are lower than for the population as a whole. Poor households spend more than 30% of their gross income on food.
Keywords: D31; I32; P46; R20; 330; Asset-Poverty; Euro Area; Income and Wealth Distribution